Pengaruh Use of Sosmed dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Melalui Variabel Intervening Efikasi Diri - Premaytri Yuwinda Athifa Dhitara; Eka Hendi Ardiansyah (Universitas Mataram, 2022)
Research motivated by the low interest in entrepreneurship students. Research see the effect use of sosmed and entrepreneurship motivation on entrepreneurship interest through self-efficacy intervening variable. Research type correlational with a quantitative approach. Sampling research as 121 students economic education study program in UNESA. Data analysis method with WarpPLS. The results are (1) use of sosmed and self-efficacy on interest in entrepreneurship partially have a significant and positive effect; (2) entrepreneurial motivation on self-efficacy partially has a significant and positive effect; (3) entrepreneurial motivation on interest in entrepreneurship partially has no significant and positive effect; (4) the use of sosmed on self-efficacy partially has no significant and positive effect; (5) simultaneously the intervening variable self-efficacy does not mediate between use of sosmed and interest in entrepreneurship, but mediates between entrepreneurial motivation variables and interest in entrepreneurship